SEWA: A framework for sociotechnical analysis of electronic health record system workarounds. (May 2019) - Blijleven, Vincent; Koelemeijer, Kitty; Jaspers, Monique
Highlights: SEWA provides a grounded foundation for performing sociotechnical analyses of EHR workarounds. SEWA defines the work system, 15 rationales, 4 attributes, and possible consequences of EHR workarounds. SEWA takes a sociotechnical angle: EHR workarounds may result from human, technical, organization, and task-related factors. SEWA can be used by researchers and practitioners to identify, analyze and resolve workarounds. Using SEWA may contribute to increased safety, quality, and efficiency of care. Abstract: Objective: To develop a conceptual framework, SEWA, to address challenges of studying workarounds emerging from Electronic Health Record (EHR) system usage. Materials and methods: SEWA is based on direct observations and follow-up interviews with physicians, nurses and clerks using their EHR at a large academic hospital. SEWA was developed by an iterative process: each new version was reviewed by experts (case study participants, hospital management, EHR developers) and refined accordingly till deemed final. Results: SEWA defines the work system and its five components constituting the context in which EHR workarounds are created. It also contains 15 rationales for creating EHR workarounds. Furthermore, four attributes are included that define EHR workarounds: cascadedness, anticipatedness, avoidability, and repetitiveness. Finally, SEWA lists the possible effects of workarounds on outcomes of clinical processes in terms of scope and impact. Discussion: SEWA provides a grounded foundation for performing sociotechnical analyses of EHR workarounds based on components of the work system. SEWA can likewise be supportive in planning redesign efforts of the work system. Finally, workarounds are subject to gradual change caused by e.g. changes in one's knowledge of the EHR, hospital policies, care directives, and system updates. Snapshots of SEWA can be taken over time and compared to gain insights into the evolution of workarounds. Conclusion: Given the absence of a sociotechnical framework to study EHR workarounds, SEWA could aid researchers and practitioners to identify, analyze and resolve workarounds, and thereby contribute to improved patient safety, effectiveness of care and efficiency of care.